Fe2O3@LaxSr1−xFeO3 Core–Shell Redox Catalyst for Methane Partial Oxidation. Issue 3 (12th February 2014) - Shafiefarhood, Arya; Galinsky, Nathan; Huang, Yan; Chen, Yanguang; Li, Fanxing
Abstract Efficient and environmentally friendly conversion of methane into syngas is a topic of practical relevance for the production of hydrogen, chemicals, and synthetic fuels. At present, methane‐derived syngas is produced primarily through the steam methane reforming processes. The efficiencies of such processes are limited owing to the endothermic steam methane reforming reaction and the high steam to methane ratio required by the reforming catalysts. Chemical looping reforming represents an alternative approach for methane conversion. In the chemical looping reforming scheme, a solid oxygen carrier or "redox catalyst" is used to partially oxidize methane to syngas. The reduced redox catalyst is then regenerated with air. The cyclic redox operation reduces the steam usage while simplifying the heat integration scheme. Herein, a new Fe2O3@LaxSr1−xFeO3 (LSF) core–shell redox catalyst is synthesized and investigated. Compared with several other commonly investigated iron‐based redox catalysts, the newly developed core–shell redox catalyst is significantly more active and selective for syngas production from methane. It is also more resistant toward carbon formation and maintains high activity over cyclic redox operations.